Trends in Domestic and Foreign Clinical Research on Ultrasound-Guided Acupuncture - Bo Hyun Kim; Tae Han Yook; Beom Yong Song; Yoo Min Choi; Jin Hyeon Shin; Sanghun Lee; Young Ju Jeon; Je Heon Noh; Jong Uk Kim (MEDrang Inc., 2018)
Background The purpose of this study was to analyze domestic and foreign clinical research into ultrasound-guidedOriental medicine acupuncture. Methods Ultrasound-guided Oriental medicine acupuncture studies were retrieved from PubMed, CNKI,KISS, NDSL, and OASIS. Results Of 6,260 articles, 17 articles were selected. There was 1 article in 2004, 1 in 2008, 2 in 2011, 1 in 2012, 4 in 2013, 3 in 2016, 2 in 2017, and 3 in 2018. Of the 17 selected articles 6 articles were studies of omalgia, 4 of knee pain and 2 of peroneal nerve palsy. In addition, there was 1 article of occipital headache, 1 of neck pain, 1 of tarsal tunnel syndrome, 1 of angioma and 1 of hiccup. In these 17 studies the ultrasound frequency range where mentioned, was 5-14 MHz. Conclusions This study provided basic data as reference for the design of more diversified and systematic clinical research in the domestic Oriental medicine community in the future.